2009
DOI: 10.1111/j.1365-2702.2009.02900.x
|View full text |Cite
|
Sign up to set email alerts
|

Structured review: evaluating the effectiveness of nurse case managers in improving health outcomes in three major chronic diseases

Abstract: The evidence generated in this review suggests that nurse case managers have the potential to achieve improved health outcomes for patients with long term conditions. Further research is required to support role development and create a more targeted approach to the intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
99
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(107 citation statements)
references
References 28 publications
5
99
1
2
Order By: Relevance
“…These models have emerged through a An evaluation of the Evercare case management pilot indicated patient and carer preference for the model compared to previous service arrangements (Boaden et al, 2006, Sargent et al, 2007. Overall , nurse-led case management may have a positive impact on clinical outcomes, quality of life and functionality (Sutherland and Hayter, 2009), and is seen by patients, carers, health and social care professionals and the case managers themselves as an effective role in meeting health and social needs of the patient (Brown et al, 2008, Chapman et al, 2009, Dossa, 2010.…”
mentioning
confidence: 99%
“…These models have emerged through a An evaluation of the Evercare case management pilot indicated patient and carer preference for the model compared to previous service arrangements (Boaden et al, 2006, Sargent et al, 2007. Overall , nurse-led case management may have a positive impact on clinical outcomes, quality of life and functionality (Sutherland and Hayter, 2009), and is seen by patients, carers, health and social care professionals and the case managers themselves as an effective role in meeting health and social needs of the patient (Brown et al, 2008, Chapman et al, 2009, Dossa, 2010.…”
mentioning
confidence: 99%
“…This result contrasts with those from previous studies, in which intervention has had a positive impact on quality of life. [17,[20][21][22] It might be that, without the intervention, quality of life for FAs would have worsened, but here it remained unchanged due to the fact that the matron took care of complex needs and provided support. Chronic diseases reported in the intervention group could also be a reason for quality of life not improving.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Studies have shown that nurse case management has a positive impact on patient self-care and adherence to treatment, quality of life and functionality, and satisfaction and service use. [18][19][20] Also, patients with peritoneal dialysis have experienced a positive effect on their wellbeing when the nurse case management model is used. These patients have been shown to demonstrate a higher quality of life and feel more energetic after nurse-led intervention.…”
Section: Introductionmentioning
confidence: 99%
“…They have also been successful in radiation oncology multidisciplinary teams as evidenced by the provision of direct patient care, involvement in specialized procedures, and conducting initial and/or follow-up visits [29]. A structured review of the literature on specialist nursing roles in chronic disease management such as diabetes, coronary heart disease and chronic obstructive respiratory disease also concluded that nurses in such roles impact positively on care coordination, quality of life and functionality and self care [30]. ( The existing nurse co-ordinator (NC) roles at the study hospital, upon which the CR role was modelled, traditionally focus on patients newly diagnosed with cancer and on those with early stage disease receiving first line treatment.…”
Section: Discussionmentioning
confidence: 99%